Analisis Mutu Pelayanan Pegawai Bappeda Kabupaten Aceh Barat Daya - Rahmi, Ulva; Yusnaidi, Yusnaidi (Jurnal Etnik: Ekonomi-Teknik, 2022)
The implementation of public services carried out by the government still does not have a special orientation regarding effectiveness and quality improvement in providing services to the community. Service quality is comprehensive and does not fully become a component of government organizations in carrying out services to the community. This study aims to see how the service quality of Bappeda employees in Aceh Barat Daya Regency is. Where, this case study was conducted in the field of data development control and planning, control, evaluation of regional development, research, and development that have not been maximized in meeting the wishes of the community by using 5 dimensions which include reliability, responsiveness, assurance, empathy, tangible, and quality. The research method used is descriptive research method with data analysis method using Importance Performance Analysis (IPA). The research sample was taken by purposive sampling totaling 50 respondents. Based on the results of the research, the conclusions that can be drawn are that all attributes have been carried out well by the Bappeda. Meanwhile, from the analysis of the gap between expectations and performance of Bappeda employees of Aceh Barat Daya Regency, none of them has exceeded consumer expectations.